Effect of orally administered cannabidiol oil on daily tonometric curve in healthy Italian Saddle horses. - Marilena Bazzano; Fulvio Laus; Matteo Cerquetella; Andrea Spaterna; Andrea Marchegiani (PLoS ONE)
Background Phytocannabinoids have the potential to lower intraocular pressure in both normal and glaucomatous eyes and they have been tested in different animal species, but not in the horse. The present paper describes the tonometric curve of healthy adult Italian Saddle horses after oral administration of cannabidiol oil (CBD). Methods CBD 20% was administered orally (oily solution) at the dose of 1 mg/kg to 8 adult horses and intraocular pressure (IOP) was evaluated by tonometric curve. Data were then compared to those of the same horses obtained the day before (blank) CBD administration. Results 15 minutes after CBD administration, IOP (time zero 27.3 ± 2.1 mmHg right eye; 24.6 ± 2.3 mmHg left eye) started to decrease (19.5 ± 5.2 mmHg right eye; 20.8 ± 2.4 mmHg left eye) and 1 hour later CBD it reached the minimum level in all horses (11.4 ± 7.5 mmHg right eye; 9.5 ± 5.8 mmHg left eye), remaining statistically significantly lower than normal values for the entire observation period (8 hours; 12.0 ± 7.9 mmHg right eye; 11.9 ± 7.8 mmHg left eye). Conclusions CBD 20% was effective to significantly reduce IOP in healthy adult Italian Saddle horses and may be an effective hypotensive agent to be implemented in case of primary or secondary glaucoma.